The methods of normativity - Hass, B (Cambridge University Press, 2017)
This essay is an examination of the relationship between phenomenology and analytic method in the philosophy of law. It proceeds by way of a case study, the requirement of compliance in Raz's theory of mandatory norms. Proceeding in this way provides a degree of specificity that is otherwise neglected in the relevant literature on method. Drawing on insights from the philosophy of art and cognitive neuroscience, it is argued that the requirement of compliance is beset by a range of epistemological difficulties. The implications of these difficulties are then reviewed for method and normativity in practical reason. A topology of normativity emerges nearer the end of the paper, followed by a brief examination of how certain normative categories must satisfy distinct burdens of proof.